Environmental criteria and indicators for assessing the optimality of the parameters of the agricultural land use system - Dorosh, Y.; Barvinskyi А.; Dorosh О.; Zastulka О.; Smolenskyi, V. (Land Management, Cadastre and Land Monitoring, 2022)
The article analyzes the current state of the regulatory framework in the field of land use and protection, which is the basis for assessing the optimality of the ecological parameters of the agricultural land use system. It was established that the vast majority of standards (optimal parameters) in the researched field are of a recommendatory nature, and therefore need to be systematized and consolidated in the relevant legal acts. The need for the structuring of ecological criteria and indicators for assessing the optimality of the parameters of the agricultural land use system, taking into account the norms of the Law of Ukraine "On Land Protection" regarding regulations in the field of land protection and reproduction of soil fertility, is substantiated. Taking into account the Law of Ukraine "On Land Protection", the division of criteria and indicators for assessing the ratio of land plots is given; criteria and indicators for assessing man-made soil pollution; criteria and indicators of soil quality assessment; criteria and indicators of land and soil degradation assessment. The optimal parameters of the ratio of land areas and the norms of assessments of the ecological state of lands caused by man-made pollution are highlighted. Optimum parameters of the volume mass of soils are indicated on the example of sod-podzolic sandy soil. Optimum parameters of the qualitative state of soils and diagnostic criteria and indicators of agrophysical and agrochemical degradation of soils are indicated. Keywords: agricultural land use, system, optimality of land use, ecological criteria and indicators.